2013
DOI: 10.1037/a0034838
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive activities and cognitive performance in middle-aged adults at risk for Alzheimer’s disease.

Abstract: Cognitive activity is thought to provide some protection against dementia, but the mechanism and timing of these effects are unknown. Data for this study were drawn from the Wisconsin Registry for Alzheimer’s Prevention (WRAP), an at-risk middle-aged sample (mean age = 54 years) enriched for parental family history of Alzheimer’s disease (AD). We had two main aims: (1) to determine the relative contribution of three facets of cognitive activity -- education, occupational complexity with data, and cognitive lei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 66 publications
4
49
0
6
Order By: Relevance
“…As for socio-demographic factors, corroborating other studies 6,20,32,40,47,48,49 , we found that more schooling significantly reduced the odds of cognitive decline.…”
Section: Discussionsupporting
confidence: 81%
“…As for socio-demographic factors, corroborating other studies 6,20,32,40,47,48,49 , we found that more schooling significantly reduced the odds of cognitive decline.…”
Section: Discussionsupporting
confidence: 81%
“…This included people at increased risk for AD due to parental family history (76.16% FH+) in both the Wisconsin Registry for Alzheimer’s Prevention (WRAP; n=127, 84.1%) and the Wisconsin Alzheimer’s Disease Research Center (WADRC; n=24, 15.9%) if they had undergone at least two DTI scans and at least one lumbar puncture. These cohorts have been described previously (Sager et al 2005; Koscik et al 2014; Racine et al 2016a; Jonaitis et al 2013). All participants were cognitively normal at study entry (MCI, AD, and other forms of dementia were excluded).…”
Section: Methodsmentioning
confidence: 99%
“…To verify the diagnosis of AD in the parent, parental medical records, autopsy reports, or results of the dementia questionnaire (Kawas, Segal, Stewart, Corrada, & Thal, 1994) were obtained and reviewed by a multidisciplinary diagnostic consensus conference (Jonaitis et al, 2013; Koscik et al, 2014; Sager et al, 2005). Absence of FH of AD was verified through detailed medical history surveys and phone interview with the participants.…”
Section: Methodsmentioning
confidence: 99%